Lipopolysaccharide Increases Immune Activation and Alters T Cell Homeostasis in SHIVB’WHU Chronically Infected Chinese Rhesus Macaque - Gao-Hong Zhang; Run-Dong Wu; Hong-Yi Zheng; Xiao-Liang Zhang; Ming-Xu Zhang; Ren-Rong Tian; Guang-Ming Liu; Wei Pang; Yong-Tang Zheng (Journal of Immunology Research)
Immune activation plays a significant role in the disease progression of HIV. Microbial products, especially bacterial lipopolysaccharide (LPS), contribute to immune activation. Increasing evidence indicates that T lymphocyte homeostasis disruptions are associated with immune activation. However, the mechanism by which LPS affects disruption of immune response is still not fully understood. Chronically SHIVB’WHU-infected Chinese rhesus macaques received 50 μg/kg body weight LPS in this study. LPS administration affected the virus/host equilibrium by elevating the levels of viral replication and activating T lymphocytes. LPS induced upregulation of CD8+ naïve T cells and downregulated the number of CD4+ and CD8+ T effector memory cells. The downregulated effector memory cells are associated with a lower frequency of monofunctional and polyfunctional cells, and an upregulated programmed cell death-1 (PD-1) expression on CD4+ and CD8+ T cells was observed in monkeys after LPS stimulation. Our data provide new insights into the function of LPS in the immune activation in SHIV/HIV infection.